Attachment, Growth, and Detachment of Human Mesenchymal Stem Cells in a Chemically Defined Medium - Salzig, Denise; Leber, Jasmin; Merkewitz, Katharina; Lange, Michaela C.; Köster, Natascha; Czermak, Peter (My University, 2016)
The manufacture of human mesenchymal stem cells (hMSCs) for clinical applications requires an appropriate growth surface and an optimized, preferably chemically defined medium (CDM) for expansion. We investigated a new protein/peptide-free CDM that supports the adhesion, growth, and detachment of an immortalized hMSC line (hMSC-TERT) as well as primary cells derived from bone marrow (bm-hMSCs) and adipose tissue (ad-hMSCs). We observed the rapid attachment and spreading of hMSC-TERT cells and ad-hMSCs in CDM concomitant with the expression of integrin and actin fibers. Cell spreading was promoted by coating the growth surface with collagen type IV and fibronectin. The growth of hMSC-TERT cells was similar in CDM and serum-containing medium whereas the lag phase of bm-hMSCs was prolonged in CDM. FGF-2 or surface coating with collagen type IV promoted the growth of bm-hMSCs, but laminin had no effect. All three cell types retained their trilineage differentiation capability in CDM and were detached by several enzymes (but not collagenase in the case of hMSC-TERT cells). The medium and coating did not affect detachment efficiency but influenced cell survival after detachment. CDM combined with cell-specific surface coatings and/or FGF-2 supplements is therefore as effective as serum-containing medium for the manufacture of different hMSC types.
Citation: Denise Salzig, Jasmin Leber, Katharina Merkewitz, Michaela C. Lange, Natascha Köster, and Peter Czermak, “Attachment, Growth, and Detachment of Human Mesenchymal Stem Cells in a Chemically Defined Medium,” Stem Cells International, vol. 2016, Article ID 5246584, 10 pages, 2016. doi:10.1155/2016/5246584